Development of an Android Grocery Checklist Application - Illahi, Ana Antoniette C.; Narag, Gershom Rob A.; Parro, Manuel Lorenzo L.; Wenceslao, Luis Paolo D. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – Grocery shopping is a regular affair in most people’s lives. With a variety of necessities such as food, toiletries, and the like being purchased whenever people go grocery shopping, shopping lists are usually made to help buyers remember and organize what they need to purchase. This research introduces a mobile application that allows users to create and manage shopping lists for grocery shopping, as well as allowing them to mark what they’ve purchased by scanning the barcode of the purchased product. It also allows users to track their stocks of purchased items as well as view their expenditures and what kinds of products take up most of their expenses. 4 Method – The barcode data used is a selection of 100 unique products taken by the researchers, and the application uses SQLite to store both checklist data and the barcodes. Result – Based on the results, all the test cases were able to pass the expected result which means that the main features of the application were able to run smoothly. There are times that the barcode scanner was not able to read the barcode properly. This scenario is seen especially when the camera is at the right angle when scanning the product’s barcode. The front angle the scanner's success rate was 99%, but from the right, left, top, and bottom, the success rate was 84%, 93%, 97%, and 94%, respectively. Although the success rate is still high, it is still preferable to scan barcodes from the front. Overall, it has an average success rate of 93.8% on all the angles. The stocks screen was able to change the number of stocks it recorded when adding and removing items from each category of item. The system was also able to display if an item was running out of stock and if it already is out of stock. It was found that the stock system's functions were working properly. The maps function was tested via changing the current area and testing if it can pin locations based on the set condition. All in all, 5 locations were tested, with each location successfully having pins on multiple locations. The charts were able to display different expenditures for different weeks and months. Conclusion – The research has resulted in the creation of an app that can help users in managing their grocery shopping. It can create and edit checklists, access, and manage checklists from the local storage, as well as add and remove items from the created checklists. The system can scan barcodes of items that are in the internal database and automatically record them in both item stocks and expenditure statistics. These can help the user in managing their shopping, as well as showing them what they need to buy and how much they are spending on certain kinds of items. The app was built at a minimum Android SDK of 16. This left the researchers with difficulties in implementing some functions due to much simpler ways of implementation added in later SDKs being unavailable, but this also meant that the app was compatible with a lot more devices. Recommendation – Organize the list of products into categories to make searching for items faster. Add an option for statistics to break down expenditures even further to individual items instead of just categories. It is also recommended to integrate the product database with different grocery stores to be more accurate in terms of getting the total price of a checklist. Practical Implication – Developing of an Android grocery checklist application for the beneficiaries is useful because it can be use and can able to track the grocery or stock the user has. Also, the application as the capability to pin the location of the available grocery store with in the area.